Modeling Klinefelter Syndrome Using Induced Pluripotent Stem Cells Reveals Impaired Germ Cell Differentiation - Botman, Olivier; Hibaoui, Youssef; Giudice, Maria G.; Ambroise, Jérôme; Creppe, Catherine; Feki, Anis; Wyns, Christine (Frontiers in Cell and Developmental Biology, 2020)
Klinefelter syndrome (KS), with an incidence between 1/600 and 1/1000, is the main genetic cause of male infertility. Due to the lack of an accurate study model, the detailed pathogenic mechanisms by which this X chromosome aneuploidy leads to KS features remain unknown. Here, we report the generation and characterization of induced pluripotent stem cells (iPSCs) derived from a patient with KS: 47XXY-iPSCs. In order to compare the potentials of both 47XXY-iPSCs and 46XY-iPSCs to differentiate into the germ cell lineage, we developed a directed differentiation protocol by testing different combinations of factors including bone morphogenetic protein 4 (BMP4), glial-derived neurotrophic factor (GDNF), retinoic acid (RA) and stem cell factor (SCF) for 42 days. Importantly, we found a reduced ability of 47XXY-iPSCs to differentiate into germ cells when compared to 46XY-iPSCs. In particular, upon germ cell differentiation of 47XXY-iPSCs, we found a reduced proportion of cells positive for BOLL, a protein required for germ cell development and spermatogenesis, as well as a reduced proportion of cells positive for MAGEA4, a spermatogonia marker. This reduced ability to generate germ cells was not associated by a decreased proliferation of 47XXY-iPSC-derived cells but rather to an increase of cell death upon germ cell differentiation as revealed by an increase of LDH release in 47XXY-iPSC-derived cells. Our study supports the idea that 47XXY-iPSCs provides an excellent in vitro model to unravel the pathophysiology and to design potential treatments for KS patients.